Potential of histamine-degrading microorganisms and diamine oxidase (DAO) for the reduction of histamine accumulation along the cheese ripening process. (October 2022) - Moniente, Marta; García-Gonzalo, Diego; Llamas-Arriba, Mª Goretti; Virto, Raquel; Ontañón, Ignacio; Pagán, Rafael; Botello-Morte, Laura
Graphical abstract: Highlights: Addition of histamine degraders reduces histamine content during cheese ripening. Certain starter cultures reduce over 40 % histamine content in long-ripened cheese. Diamine oxidase enzyme reduced histamine content at the onset of cheese ripening. Histamine degraders did not affect physicochemical properties of cheeses. Cheeses with histamine degraders had a particular, not unpleasant aroma. Abstract: Lentilactobacillus parabuchneri is the main bacteria responsible for the accumulation of histamine in cheese. The goal of this study was to assess the efficiency of potential histamine-degrading microbial strains or, alternatively, the action of the diamine oxidase (DAO) enzyme in the reduction of histamine accumulation along the ripening process in cheese. A total of 8 cheese variants of cow milk cheese were manufactured, all of them containing L. parabuchneri Deutsche Sammlung von Mikroorganismen 5987 (except for the negative control cheese variant) along with histamine–degrading strains ( Lacticaseibacillus casei 4a and 18b; Lactobacillus delbrueckii  subsp . bulgaricus Colección Española de Cultivos Tipo (CECT) 4005 and Streptococcus salivarius  subsp.  thermophilus CECT 7207; two commercial yogurt starter cultures; or Debaryomyces hansenii ), or DAO enzyme, tested in each cheese variant. Histamine was quantified along 100 days of cheese ripening. All the degrading measures tested significantly reduced the concentration of histamine. The highest degree of degradation was observed in the cheese variant containing D. hansenii, where the histamine content decreased up to 45.32 %. Cheese variants with L. casei, or L. bulgaricus and S. thermophilus strains, also decreased in terms of histamine content by 43.05 % and 42.31 %, respectively. No significant physicochemical changes (weight, pH, water activity, color, or texture) were observed as a consequence of the addition of potential histamine-degrading adjunct cultures or DAO in cheeses. However, the addition of histamine-degrading microorganisms was associated with a particular, not unpleasant aroma. Altogether, these results suggest that the use of certain histamine-degrading microorganisms could be proposed as a suitable measure in order to decrease the amount of histamine accumulated in cheeses.